The cicadas (Hemiptera: Cicadidae) of Ecuador including the description of five new species, a new subtribe, four new synonymies, and fifteen new records - Sanborn, Allen F. (Zootaxa, 2020)
The known cicada fauna of Ecuador is identified. Durangona exechopyga n. sp., Calyria chaetoacontia n. sp., Calyria xiphion n. sp., Carineta coronida n. sp., and Carineta tiarata n. sp. are described as new. The subtribe Plautillina Distant, 1905h rev. stat. is formed for the genera Plautilla Stål, 1865 and Onoralna Boulard, 1996 within the Zammarini Distant, 1905b. Zammara erna Schmidt, 1919 n. syn., Orellana brunneipennis Goding, 1925 n. syn. and Orellana pulla Goding, 1925 n. syn. are reported to be junior synonyms of Zammara intricata Walker, 1850 and Coata facialis var. Jacobi 1907a n. syn. is shown to be unavailable and a junior synonym of Coata facialis Distant 1906b. The first records of Fidicinoides besti Boulard & Martinelli, 1996, Fidicinoides brunnea Boulard & Martinelli, 1996, Fidicinoides descampsi Boulard & Martinelli, 1996, Fidicinoides ptychodiropeda Sanborn 2020b, Ariasa bilaqueata (Uhler, 1903), Guyalna bicolor (Olivier, 1790), Guyalna dyticamazona Sanborn, 2020b, Calyria fenestrata (Fabricius, 1803), Taphura boulardi Sanborn, 2011a, Carineta lichiana Boulard, 1986a, Carineta peruviana Distant, 1905c, Carineta producta Walker, 1858b, Carineta rufescens (Fabricius, 1803), Herrera concolor Sanborn, 2019b and Toulgoetalna tavakiliani Boulard, 1982 are provided. The new records represent the first records for Ariasa Distant 1905d, Calyria Stål, 1862, the tribe Parnisini Distant, 1905e, and Toulgoetalna Boulard, 1982, in Ecuador. The record for Calyria fenestrata is the first known specific locality for the species. An additional first record of Fidicinoides besti is provided for Colombia to expand the known distribution of this species. Previous records of Zammara calochroma Walker, 1858a, Dorisiana semilata (Walker, 1850), Carineta bilineosa Walker, 1858b, Carineta fasciculata (Germar, 1821), and Selymbria stigmatica (Germar, 1834) are considered to be misidentifications of Dorisiana metcalfi Sanborn & Heath, 2014 (= Cicada viridis Olivier, 1790), C. maculosa Torres, 1848, C. pilifera Walker, 1858a, and S. ecuadorensis Sanborn, 2019a, respectively, so that Z. calochroma, D. semilata, C. bilineosa, C. fasciculata, and S. stigmatica are removed from the cicada fauna of Ecuador. In addition, Chilecicada occidentis (Walker, 1850) is removed from the Ecuadorian cicada fauna as the species is restricted to Chile. The currently known Ecuadorian cicada fauna is comprised of 98 species from 24 genera, nine tribes and three subfamilies.